Case Study of Roof Behaviour and Conditions for Longwall Face Recoveries at Beltana No. 1 Mine, Australia - David Hill (International Conference on Ground Control in Mining, 2011)
Over the last decade, Beltana No.1 Mine has generally been Australia?s most productive longwall operation, with a ROM output of 7.2 Mt in YEJ2007. Characteristically favorable roof conditions and low depths of cover resulted in typically high rates of development drivage and longwall retreat. As a consequence of these high rates of development and extraction, there was a continuing focus on recovering and relocating the longwall face as efficiently as possible to minimize associated production delays and operational costs. This paper presents a comprehensive case study of the conventional longwall recoveries (?take-offs?) at the mine, from Longwall 1 to 14. By examining the take-off monitoring data collected over the life of the mine, the key geotechnical issues are demonstrated, including their relationship to the ground behavior experienced and the issues overcome.